DEVELOPMENT OF ANALYSIS METHOD OF METRONIDAZOLE USING FTIR (FOURIER TRANSFORM INFRA RED) METHOD AND COMPARED TO UV-VIS SPECTROPHOTOMETRIC METHOD - Irsyad Aliah, Ahmad
The analysis method of a drug active substance is now highly developed, it aims to find a more practical method and provide more accurate results. Metronidazole assay analysis has been performed in tablet preparations using Fourier Transform Infra Red (FTIR) method and compared to UV-VIS spectrophotometric method. This study aimed to develop an effective and efficient method in analyzing metronidazole compounds and to ensure that this method is suitable to be done routinely. In finding a suitable method, both of this methods are compared in terms of analysis parameters, practicality, and cost required. The result of analysis parameter showed that FTIR method has regression coefficient value (r) 0.99985, coefficient of regression variance (Vx0) 1.1001%, percent recovery at concentration 3.2; 4; and 4.8% respectively 100.35 ± 0.43%; 99.43 ± 0.93%; and 99.91 ± 0.25%, Relative Standard Deviation (RSD) 0.19%, and LOD and LOQ respectively 0.00012% w/w and 0.00039% w/w. Meanwhile, the UV-VIS spectrophotometric method has value of regression coefficient (r) 0.99975, coefficient of regression variance (Vx0) 0.9924%, percent recovery at concentration 9.6; 12; and 14.4% respectively 99.27 ± 0.84%; 98.06±0.41%; and 101.95 ± 0.25%, Relative Standard Deviation 0.80%, and LOD and LOQ respectively 0.36 ppm and 1.19 ppm. In terms of effectiveness, FTIR method is relatively more practical and easy, is evidenced by processing time that shorter than UV-VIS spectrophotometric method, while in terms of cost, FTIR method requires relatively less cost. It can be concluded that the FTIR method is more accurate, precise, praticality, and relatively cheaper and easier.